CBCT Evaluation of Maxillary Incisive Canal Characteristics Among Population in Regard to Possibility of Implant Cortical Anchorage—A Multicenter Study - Fodor Calin; Bartosz Dalewski; Maciej Ellmann; Paweł Kiczmer; Stefan Ihde; Marta Bieńkowska; Jacek Kotuła; Łukasz Pałka (Dentistry Journal)
Background/Objectives: Implant placement in cases of severe bone atrophy or compromised alveolar bone requires careful planning, especially in the anterior maxilla. The nasopalatine canal (NPC) and its cortical walls offer potential anchorage sites. This study evaluates the NPC’s anatomical characteristics using cone beam computed tomography (CBCT) to assess its suitability for implant anchorage. Methods: A retrospective analysis of 150 CBCT scans from three dental clinics in Poland was conducted. NPC measurements—including length, width, number of canals, and distances to adjacent anatomical structures—were taken in the sagittal, coronal, and axial planes. Statistical tests included Pearson correlation and Student’s t-test to explore relationships between NPC dimensions and gender. Results: The mean NPC length was 10.27 mm and mean width 3.55 mm. Significant gender differences were observed in the canal length, width, and distances to the labial and palatal plates (p < 0.05). Strong positive correlations were found between the canal width at the palate base and other parameters, such as the midpoint width (r = 0.58) and diameter (r = 0.44). The distance from the palatal opening to the labial plate showed the strongest correlation (r = 0.67), indicating enhanced cortical anchorage potential with increased canal dimensions. Discussion: NPC morphology varied (cylindrical, funnel-like, hourglass), aligning with prior studies. Larger diameters were linked to single-canal configurations. Implant placement strategies—such as direct canal insertion or lateralization—can be effective, especially with polished, single-piece implants that reduce soft tissue ingrowth and improve primary stability. Conclusions: Understanding NPC anatomy is crucial for implant planning in atrophic maxillae. With the proper technique, NPC use for cortical anchorage is a viable treatment option.